General budget support, health expenditures, and neonatal mortality rate: A synthetic control approach - Kaisa Alavuotunki (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
I examine impacts of general budget support in 12 countries using the synthetic control approach. First, I analyse changes in government expenditures on health before and after the introduction of budget support. Second, I look at neonatal mortality (a presumed proxy for improvements in health services), concentrating on the countries that increased their health spending following the introduction of general budget support. The results indicate that, at least in Tanzania, Burkina Faso, Rwanda, and Malawi, budget support did have a positive effect on health spending and, except for Rwanda, neonatal mortality rate declined relatively faster than in the synthetic control countries.
Keywords: H51; F35; O57; 330; general budget support; health sector expenditures; neonatal mortality; developing countries; synthetic control method